Effect of 2002 FIFA World Cup: Point of Attachment That Promotes Mass Football Participation - Kang, Taeahn; Hahm, Jeongbeom; Matsuoka, Hirotaka (Frontiers in Psychology, 2022)
The 2002 FIFA World Cup Korea/Japan significantly promoted football in the host countries. However, it remains unclear how the event has changed mass football (soccer in North America) participation. This study applies points of attachment (POA)—a well-developed concept in the field of sport management—to the 2002 FIFA World Cup and aims to examine which specific POA promoted football participation frequency immediately after the event and the present frequency of football participation in the host countries. An online questionnaire survey was conducted in South Korea (n = 405) and Japan (n = 398). The samples included adults aged >19 as of the hosting date of the 2002 World Cup. Hierarchical regression analyses were performed to test all the datasets by employing four POAs (players, coaches, national teams, and football) as independent variables. Multiple control variables (e.g., nationality and age) and two dependent variables (football participation frequency immediately after the event and the present frequency of football participation) were included in the model. Correspondingly, those who had a higher attachment to each point during the event showed a higher frequency of football participation immediately after the event. In contrast, only two POAs (players and coaches) led to a higher frequency of present football participation. These findings provide the first empirical evidence highlighting the influence of the 2002 FIFA World Cup on mass football participation depending on the POA.